Effect of Variation Substitution of Nd and Eu on the Crystal Structure of Y-124 Superconductor (Y1-x-yNdxEuyBa2Cu4O8??) - Jalut, Laura Laudensia Senly; Suharta, Wayan Gede; Windaryoto, Windaryoto (BULETIN FISIKA, 2021)
In this study, the substitution of elements Nd and Eu on the superconductor Y 1-x-y Nd x Eu y Ba 2 Cu 4 O 8?? (Y-124) has been carried out using compounds Y 2 O 3 , BaCO 3 , CuO, Nd 2 O 3 and Eu 2 O 3 with molar variations of Nd (x) and Eu (y), respectively. 0, 0,05, 0,1, 0,15 and 0,2 respectively to determine the effect of Nd and Eu substitution on the volume fraction and crystal structure of the superconducting Y-124. Samples were synthesized using wet mixing method with HNO 3 as solvent, followed by calcination process at 600 o C for 3 hours and sintering process at 900 o C for 10 hours. Analysis of the structure of the superconducting Y-124 was carried out by characterizing X-ray Diffraction (XRD) and Fourier-Transform Infrared Spectroscopy (FTIR). The results of XRD characterization showed a fine and sharp spectrum which indicated that crystallization had occurred completely. The resulting spectrum was dominated by the Y-124 phase and a small percentage of the impurities were detected. Substitution of Nd and Eu elements resulted in volume fractions of 82,7 %, 83,6 %, 84,4 %, 87,0 % and 85,9 %, respectively. The volume fraction value increased with the addition of Nd and Eu from 0 to 0,15, then decreased at 0,2. This indicates that the optimization of the addition of Nd and Eu is at a value of 0,15 in the molar ratio of compounds. The substitution of Nd and Eu elements also causes changes in the lattice parameters towards the a-axis with values between 3,7549 and 3,8323 , towards the b-axis with values between 3,8094 and 3,8425 , and towards the c-axis with values between 26,7390 and 26,8970. The FTIR results show the presence of an absorption band in the YBCO region, but the sample still contains impurities which are indicated to come from BaCO 3 and HNO 3 .